Boko Haram’s Factional Feuds: Internal Extremism and External Interventions - Zenn, Jacob (Terrorism and political violence, 2021)
This article examines the factions, leadership, and internal organization of Boko Haram, the terrorist group which has operated to devastating effect in parts of northern Nigeria, Niger, Chad, and Cameroon. It finds the group’s leadership has been significantly more centralized than previous literature has acknowledged. The leadership was also extremely ruthless but enforced group cohesion by killing anyone who sought to defect. Group members attempted to defect and depose the leadership in 2012 and 2016 by seeking external interventions from Al Qaeda in the Islamic Maghreb (AQIM) and the Islamic State of Iraq and the Levant (ISIL), respectively. In the first instance Boko Haram’s leadership demonstrated control and influence by forcing defectors back into submission, but in the second instance ISIL-backed militants deposed the leadership in a rebellion and coup. The loyalty to ISIL of jihadist commanders and foot soldiers in Nigeria explains why only the rebellion and coup succeeded in 2016 even though AQIM provided greater material support to the first set of defectors in 2012. This article contributes to research on internal dynamics of Boko Haram, the relationships between Al Qaeda and ISIL and their allied and affiliated organizations, and the costs and benefits of extreme leadership for terrorist groups.